2016
DOI: 10.12740/pp/61569
|View full text |Cite
|
Sign up to set email alerts
|

Incidence of postpartum depression and couple relationship quality

Abstract: Patients dissatisfied with the quality of their marital relationship experienced an increased severity of postpartum depression symptoms. Greater satisfaction with relationship quality was expressed by women in formalized relationships.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
20
0
6

Year Published

2018
2018
2024
2024

Publication Types

Select...
7
2
1

Relationship

0
10

Authors

Journals

citations
Cited by 46 publications
(27 citation statements)
references
References 0 publications
1
20
0
6
Order By: Relevance
“…Similar to our results, in a prospective study conducted by Malus et al, authors reported a greater severity of postpartum depression symptoms in women with poor marital relationship quality (43).…”
Section: J O U R N a L P R E -P R O O Fsupporting
confidence: 92%
“…Similar to our results, in a prospective study conducted by Malus et al, authors reported a greater severity of postpartum depression symptoms in women with poor marital relationship quality (43).…”
Section: J O U R N a L P R E -P R O O Fsupporting
confidence: 92%
“…This is not surprising, given the high comorbidity of postpartum PTSD with postpartum depression ( Czarnocka and Slade, 2000 ; Grekin and O’Hara, 2014 ). Furthermore, postpartum depression has previously been shown to be associated with poorer postpartum marital relationship satisfaction ( Wenzel et al, 2005 ) and perceived couple relationship quality ( Malus et al, 2016 ). Negative cognitions typical for depression are likely to affect the perception of the couple relationship.…”
Section: Discussionmentioning
confidence: 99%
“…In turn, Charline El-Hachem did not observe any signi cant impact of relationship status on the prevalence of postpartum depression among single women [23]. Małus et al reported that women who were more satis ed with their relationships were characterized by better psychological condition after giving birth [24]. Umuziga et al found more severe symptoms of mood disorders after giving birth among respondents having four or more children, who had a poor relationship with their partner, compared to those who only had one child [25].…”
Section: Discussionmentioning
confidence: 94%